PERBANDINGAN PAPARAN ASAP ROKOK KONVENSIONAL DAN ROKOK HERBAL PADA MENCIT (Mus musculus) TERHADAP PERBANDINGAN GAMBARAN HISTOLOGI PARU - Nurul Hidayah; Olan Rahayu Puji Astuti Mussa; Rondius Solfaine; Yudha Sapto Utomo (VITEK : Bidang Kedokteran Hewan, 2020)
The purpose of this study was to determine the comparison of conventional cigarette smoke and herbal cigarettes against histological damage in the lungs of mice. The research method uses a completely randomized design with 21 mice aged 8-12 weeks and divided into 3 treatment groups. Group P0 was not given exposure to cigarette smoke, group P1 was exposed to conventional cigarette smoke tar content was 39 mg nicotine 2 mg, group P2 was exposed to herbal cigarette smoke tar content was 41.60 mg nicotine 1.64 mg. On the 15th day the mice were deuthanated for pulmonary extraction and haematoxyline eosin staining was made. Data analysis using one way ANOVA. The results of this study obtained scoring lung damage to edema lesions in P0, P1, P2 Sig 0.246 (p> 0.05). Inflammation of inflammatory cells at P0, P1, P2 Sig 0.000 (p <0.05). Destruction of alveolar septum at P0, P1, P2 Sig 0.000 (p <0.05). The conclusion of this study is the difference in lung damage in mice in the form of edema, infiltration of inflammatory cells, destruction of the alveolar septum between exposure to conventional cigarette smoke and herbal cigarettes. The purpose of this study was to determine the comparison of conventional cigarette smoke and herbal cigarettes against histological damage in the lungs of mice. The research method uses a completely randomized design with 21 mice aged 8-12 weeks and divided into 3 treatment groups. Group P0 was not given exposure to cigarette smoke, group P1 was exposed to conventional cigarette smoke tar content was 39 mg nicotine 2 mg, group P2 was exposed to herbal cigarette smoke tar content was 41.60 mg nicotine 1.64 mg. On the 15th day the mice were deuthanated for pulmonary extraction and haematoxyline eosin staining was made. Data analysis using one way ANOVA. The results of this study obtained scoring lung damage to edema lesions in P0, P1, P2 Sig 0.246 (p> 0.05). Inflammation of inflammatory cells at P0, P1, P2 Sig 0.000 (p <0.05). Destruction of alveolar septum at P0, P1, P2 Sig 0.000 (p <0.05). The conclusion of this study is the difference in lung damage in mice in the form of edema, infiltration of inflammatory cells, destruction of the alveolar septum between exposure to conventional cigarette smoke and herbal cigarettes.